USE MULTIPLEX REALTIME PCR METHODS FOR RAPID DETECTION OF FIVE BACTERIAL PATHOGENS CAUSING NOSOCOMIAL INFECTION: STAPHYLOCCCUS AUREUS, ESCHERICHIA COLI, PSEUDOMONAS AERUGINOSA, KLEBSIELLA PNEUMONIAE, ACINETOBACTER BAUMANNII ISOLATED FROM RESPIRATORY SAMPL (Vietnam Journal of Community Medicine, 2021)
Purposes: Using the multiplex realtime PCR assay to simultaneously detect five nosocomial pathogens: Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Acinetorbacter bauminnii isolated from respiratory specimens. Objectives and Methods: 47 respiratory specimens from patients were treated at Thanh Nhan and Duc Giang hospitals as nosocomial infection. The patient samples were divided into 2 parts, one part was used for culture test and the other part was performed by multiplex real-time PCR assay. Results: 40/47 samples were positive (85.1%), the multiplex real-time PCR method can simultaneously detect 5 nosocomial pathogens from respiratory specimens, similarity coefficient with the culture method is 0.97 (p
Keywords: Respiratory specimens, Multiplex real-time PCR, nosocomial infection, nosocomial pathogens.